Experiences of student circus arts performers undertaking a shoulder rehabilitation program via telehealth consultation during the COVID-19 pandemic - Barradell, S.; Ganderton, C.; Knowles, S.; Munro, D.; Rayner, A.; Watson, L. (Journal of Science and Medicine in Sport, 2021)
Background: The Coronavirus pandemic (COVID-19) has brought about significant change to athletes, with the postponement and cancellation of competitions and performances. This has created a need to proactively adapt to ensure peak mental and physical fitness. This requirement to adapt may be even more relevant for those athletes rehabilitating from injury during the pandemic. This qualitative study sought to explore the experiences of student circus arts performers with atraumatic shoulder instability undertaking a 12-week shoulder rehabilitation program during the Melbourne COVID-19 pandemic lockdown. Method: Fourteen circus arts students from the National Institute of Circus Arts were interviewed via teleconsultation. Semi-structured interviews were recorded, transcribed and analysed using inductive thematic analysis. Results: Five overarching themes were identified: impact (physical and mental), opportunity, developing routine, client-therapist relationship, and transformation. All participants reported positive physical changes to their shoulder including increases in strength, stability, range of motion, less pain, "clicking" and "clunking", improved posture, muscle memory as well as carry-over to functional circus activities. The pandemic`s mental impact varied across the cohort, with positive and negative experiences described in relation to cognitive, social and affective factors. Most performers felt the pandemic provided an opportunity to focus on rehabilitation of their shoulder. Program effects were underpinned by positive client-therapist relationships and a progressive transformation of learning where students gained knowledge, and strategies for short and long-term management of their condition. Discussion: The COVID-19 pandemic provides a unique opportunity for individuals to undertake injury rehabilitation during an absence of usual training and performance. Rehabilitation for atraumatic shoulder instability can be delivered effectively via teleconsultation to improve subjectively reported physical function and long-term management of atraumatic shoulder instability, facilitated by strong client-therapist relationships and a structured rehabilitation program.